2020
DOI: 10.3390/molecules25081939
|View full text |Cite
|
Sign up to set email alerts
|

Higher Gene Expression Related to Wound Healing by Fibroblasts on Silk Fibroin Biomaterial than on Collagen

Abstract: Silk fibroin (SF), which offers the benefits of biosafety, biocompatibility, and mechanical strength, has potential for use as a good biomedical material, especially in the tissue engineering field. This study investigated the use of SF biomaterials as a wound dressing compared to commercially available collagen materials. After human fibroblasts (WI-38) were cultured on both films and sponges, their cell motilities and gene expressions related to wound repair and tissue reconstruction were evaluated. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…On day 14, we found ECM-related GO terms, such as “extracellular matrix organization” and “collagen catabolic process,” and GO terms related to cell migration and proliferation, such as “positive regulation of cell migration” and “positive regulation of cell proliferation” ( Figure 2 C, Table S3 ). Thus, gene expression changes in collagen discs are similar to those occurring in scar tissues in vivo [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…On day 14, we found ECM-related GO terms, such as “extracellular matrix organization” and “collagen catabolic process,” and GO terms related to cell migration and proliferation, such as “positive regulation of cell migration” and “positive regulation of cell proliferation” ( Figure 2 C, Table S3 ). Thus, gene expression changes in collagen discs are similar to those occurring in scar tissues in vivo [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main stages of cell growth on the biomaterial surface include cell adhesion, proliferation, differentiation and ECM formation, and these stages are regulated by different tissue repair-related genes ( Hashimoto et al, 2020 ). COL-I is the main structural component of dermal tissue, and is higher in the dermis of normal skin, and COL-1 content can affects skin structure, function, and texture characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, Scheibel et al established a silk protein based on the consensus sequence of A. diadematus Fibroin 4 (eADF4(C16); MW 48 kDa) (Huemmerich et al 2004, Petzold et al 2017, Saric and Scheibel 2019, Salehi et al 2020. In previous studies, we and others, have demonstrated that silk-based scaffolds are biocompatible without provoking immunological reaction (Zeplin et al 2014, Ju et al 2016, Zhang et al 2017, Steiner et al 2019, Hashimoto et al 2020, Kramer et al 2020. In the present study we were able to show macrophages at the interface between the newly formed tissue and eADF4(C16) hydrogels.…”
Section: Discussionmentioning
confidence: 99%